2022
DOI: 10.1111/1750-3841.16228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginger extract and its major component 6‐gingerol on anti‐tumor property through mitochondrial biogenesis in CD8+ T cells

Abstract: Ginger extract (GE) and its major component 6-gingerol (6G) have been reported to exert anti-tumor effects in various cancers. The underlying mechanism, however, has not been well demonstrated. Here, we have focused on the relationship between promotion of mitochondrial biogenesis in tumor infiltrating CD8 + T cells induced by GE and 6G and their cytotoxic effect. The results showed that GE induced 56% inhibition of tumor growth in Lewis lung carcinoma (LLC) xenograft mouse model and 6G induced 33% (25 mg/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In another study, 6-gingerol combined with tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) increased TRAIL-induced cell death in human lung cancer (A549) cells by an enhanced accumulation of microtubule-associated protein light chain 3-II and p62, establishing inhibition of autophagy flux ( Nazim et al, 2015 ). In the study by Deng et al (2022) , it was also found that 6-gingerol increased cytotoxicity of CD8+T cells against tumor cells by promoting mitochondrial biogenesis in CTLL-2 (cytotoxic T cells) cells.…”
Section: Interaction Of Gingerols With the Immune Systemmentioning
confidence: 95%
“…In another study, 6-gingerol combined with tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) increased TRAIL-induced cell death in human lung cancer (A549) cells by an enhanced accumulation of microtubule-associated protein light chain 3-II and p62, establishing inhibition of autophagy flux ( Nazim et al, 2015 ). In the study by Deng et al (2022) , it was also found that 6-gingerol increased cytotoxicity of CD8+T cells against tumor cells by promoting mitochondrial biogenesis in CTLL-2 (cytotoxic T cells) cells.…”
Section: Interaction Of Gingerols With the Immune Systemmentioning
confidence: 95%
“…Ginger is used in traditional medicine for a variety of illnesses, as it demonstrates anti-inflammatory, antioxidant, anti-platelet, anti-emetic, anti-ulcer, anti-cancer, antihyperglycemic and antilipidemic properties. 18 , 19 The major constituents of ginger are gingerols and shogaols, respectively, to which its medicinal properties are attributed. 20 According to several studies, these two bioactive constituents exhibited anti-obesity effects in both animal experiments and human trials.…”
Section: Introductionmentioning
confidence: 99%
“…Ginger ( Zingiber officinale Roscoe), belonging to the genus Zingiber , is one of the most popular spices used in food processing in China. Ginger is widely cultivated in southeastern and southwestern of China and has been employed as a traditional medicine for treatment of vomiting, tumor, indigestion, and oxidative stress. Previous phytochemical studies of ginger revealed it contains several secondary metabolites including gingerols, polysaccharides, terpenoids, volatile oils, and diarylheptanoids. The results of previous investigations show that extracts and chemical constituents in ginger display extensive pharmacological effects including anti-inflammatory, antifibrosis, antibacterial, and antitumor activities . Previous efforts have mainly focused on fresh and dried ginger, but the bioactive natural components of ginger peel, which is often discarded in processing and environmentally harmful affecting, have been rarely explored.…”
Section: Introductionmentioning
confidence: 99%
“…5−8 The results of previous investigations show that extracts and chemical constituents in ginger display extensive pharmacological effects including antiinflammatory, 7 antifibrosis, 9 antibacterial, 10 and antitumor activities. 11 Previous efforts have mainly focused on fresh and dried ginger, but the bioactive natural components of ginger peel, which is often discarded in processing and environmentally harmful affecting, have been rarely explored. In our previous studies, 12,13 we found that ginger peel contains various types of chemical components, many of which can significantly reduce the rate of apoptosis and increase survival of normal human lung bronchial epithelial cells.…”
Section: ■ Introductionmentioning
confidence: 99%